Science and Technology Women Farmers' Through Grape Cultivation (Vitis vinifera L) - Herdiana, Herdiana; Mappanganro, Nurlailah; Nirmawati, Nirmawati (Unram Journal of Community Service, 2025)
Women farmers are a group of women who work as farm laborers and housewives. Low education and minimal skills prevent them from getting better jobs. Developing the quality of women farmers through non-formal education is important to increase knowledge and skills so that they can live better. Grape cultivation by utilizing existing empty land is one of the solution approaches provided to create new businesses among women farmers groups. Community partnership service activities that will be carried out focus on coaching and mentoring women farmers groups through increasing knowledge and technology of grape cultivation. The purpose of this community partnership service activity is to provide education about grape cultivation and propagation of grape plants. The location of the service is in Jurang Are hamlet, Bonder Village, Praya Barat District, Central Lombok Regency-NTB which will be carried out for 1 year from January to December 2024 with 10 KWT DeBoRaTif_Man partners. The output of the service is a national journal accredited by SINTA 4 in the UAJS journal. The result of the Community Partnership Service activity is the formation of cooperation partners who will be assisted until they become independent partners in grape cultivation. This PKM activity consists of counseling and training activities. In the future, partners really hope for the sustainability of this activity so that they can be independent and make the results of this activity into new business opportunities